Effect of initiation-inhibition and handedness on the patterns of the P50 event-related potential component: a low resolution electromagnetic tomography study - Capsalis Christos N; Maganioti Argiro E; Hountala Chrissanthi; Nanou Eleni D; Rabavilas Andreas; Beratis Ion N; Papadimitriou George N; Papageorgiou Charalabos (Behavioral and Brain Functions, 2009)
Abstract Background Recent research recognizes the association between handedness, linguistic processes and cerebral networks subserving executive functioning, but the nature of this association remains unclear. Since the P50 event related potential (ERP) is considered to reflect thalamocortical processes in association with working memory (WM) operation the present study focuses on P50 patterns elicited during the performance of a linguistic related executive functioning test in right- and left-handers. Methods In 64 young adults with a high educational level (33 left-handed) the P50 event-related potential was recorded while performing the initiation and inhibition condition of a modified version of the Hayling Sentence Completion test adjusted to induce WM. The manual preference of the participants was evaluated with the use of the Edinburgh Handedness Inventory (EHI). Results P50 showed greater amplitudes in left- than in right-handers, mainly in frontal leads, in the initiation condition. Reduced amplitudes in inhibition compared to initiation condition were observed in left-handers. Low Resolution Electromagnetic Tomography (LORETA) analysis showed lower frontal lobe activation in the inhibition than in the initiation condition in both right- and left-handers. Also, LORETA yielded that right-handers exhibited greater activation in the inhibition condition than left-handers. Additionally, LORETA showed assymetrical hemispheric activation patterns in right-handers, in contrast to symmetrical patterns observed in left-handers. Higher P50 amplitudes were recorded in right-hemisphere of right-handers in the initiation condition. Conclusion Brain activation, especially the one closely related to thalamocortical function, elicited during WM operation involving initiation and inhibition processes appears to be related to handedness.